The EFFECT OF PARTICIPATION IN PREGNANT WOMEN'S CLASSES ON PRIMIGRAVIDA ANXIETY LEVELS IN FACING CHILDBIRTH AT PAJARAKAN HEALTH CENTER - Fifil Sumarni Sumarni; Erma Sulistyaningsih Sulistyaningsih; Leersia Yusi Ratnawati Ratnawati (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2022)
avida in dealing with childbirth at the Pajarakan Health Center. This study uses a pre-experimental research type with a one-group pre-post test design. The study location is in the Pajarakan Health Center, Probolinggo Regency. The population is primigravida mothers in the Pajarakan Health Center area of ​​30 people and the number of samples is 30 people. The sampling technique is non-probability sampling with purposive sampling method. Primary data was obtained by using a questionnaire, secondary data from the Probolinggo District Health Office and Pajarakan Health Center. The independent variable (independent) is the class of pregnant women, the dependent variable (dependent) is anxiety. Data were analyzed using SPSS 26 software for univariate and bivariate. The results of the study describe the characteristics of the majority of respondents aged 20-35 years, the most educational history of undergraduate education, the average family income between 2.5 million - 3.5 million and all respondents attended four class meetings of pregnant women. Respondents' anxiety before taking classes for pregnant women was mostly severe anxiety, the knowledge of respondents before attending classes for pregnant women had a fairly good level of knowledge, the attitude of respondents before taking classes for pregnant women was positive. This indicates that the participation of pregnant women affects the level of anxiety of pregnant women in facing childbirth.   Keywords: anxiety, Health Cente,  participation, pregnant women', and primigravid